Utilization of hepatitis B virus surface antigen positive grafts in liver transplantation: A matched study based on a national registry cohort. Issue 6 (23rd March 2022) - Yu, Songfeng; Cen, Chao; Zhang, Xuanyu; Cheng, Longyu; Xia, Weiliang; Jia, Junjun; Ye, Yufu; Yu, Jun; Zhang, Min; Shen, Yan; Zheng, Shusen
Abstract: Background and Aim: Donor shortage has become worldwide limitation in liver transplantation (LT). Use of hepatitis B virus surface antigen positive (HBsAg+) donors could be an alternative source of donor organs. This study aims to investigate the safety and efficacy of LT using HBsAg+ liver grafts and associated long‐term outcome. Methods: This was a retrospective study of adults LT registered in the database of the China Liver Transplant Registry between January 2015 and September 2018. By propensity score matching (1:1), 503 eligible patients who received HBsAg+ liver grafts were compared with 503 matched patients who received HBsAg− liver grafts. Results: The 1‐, 3‐, and 5‐year patient survival rates were 81.52%, 72.04%, and 66.65% in HBsAg+ donor group, which were comparable with 83.93%, 77.27%, and 65.73% in HBsAg− donor group ( P  = 0.222). The 1‐, 3‐, and 5‐year graft survival rates were also comparable between the two groups (81.49%, 71.45%, and 67.26% vs 83.62%, 77.11%, and 65.81%, respectively, P  = 0.243). Most main complications were not increased in HBsAg+ donor group except for the retaining of HBsAg positivity after LT. Furthermore, transplanting HBsAg+ liver grafts did not result in inferior outcomes either in HBsAg+ or HBsAg− recipients. The risk of tumor recurrence after LT was not increased in hepatocellular carcinoma patients. Conclusions: The outcomes of using HBsAg+ liver grafts were comparable with those of HBsAg− liver grafts. Our study provided strong evidence for the safe use of HBsAg+ grafts in LT to expand the donor liver pool.